PERUBAHAN POLA KEHIDUPAN SUKU HUTAN DI KAMPUNG NERELANG KABUPATEN KEPULAUAN MERANTI SEBELUM DAN SESUDAH TAHUN 2004 - Fitri Triska Fitri Triska; Isjoni '; Tugiman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Forest Tribe Society is a society that is trying the traditions and values of the confidence that comes from their ancestors, on the one hand it is possible to isolate themselves from the hold changes and road resistance to change that desire in society to go to maintain. But in fact they can not get away from change itself shy, whether it comes from within their own community, which began to break out of their customary rules, population growth, changes in their physical nature and the limited size of their basic needs, as well as the many influences to meet outside as well as the role of government and the interaction with the outside world community causes changes in society inevitably Forest Tribe. The purpose of the investigation to determine the causes of the change in the pattern of life in the forest tribe Nerelang and to know which aspects of the aspects that change in the community forest tribe. This research method is quantitative descriptive method. Location of the study is the village Nerlang Tohor River Village West District of the East High Cliff. When to study for 3 months from the beginning to the exam thesis proposal seminar. The technique of collecting data using interviews, observations, questionnaires and documentation, and a table with the data in the form of cross tab. Results of the study in general researchers can say changing patterns of forest tribe lives caused by changing natural environmental factors, population growth, the influence of outside cultures and new discoveries, while aspects that change the lives of forest tribe is the social aspect, the aspect economic and educational aspects.Keyword: Change, Patterns of Life, Forest Tribe